The predictive value of the clinical sign of limited hip abduction for developmental dysplasia of the hip (DDH) - Svemir Čustović; Sahmir Šadić; Aleksandar Vujadinović; Asmir Hrustić; Mahir Jašarević; Amer Čustović; Ferid Krupić (Medicinski glasnik, 2018)
Aim: To assess the relationship between the clinical sign of limited hip abduction and developmental dysplasia of the hip (DDH). Methods: A research was conducted on 450 newborns at the Neonatal Unit at the Clinic of Gynaecology and Obstetrics and the Orthopaedics and Traumatology Clinic of the University Clinical Centre, Tuzla, between 30 th August 2011 and 30 th April 2012. Clinical (degree of hip abduction) and ultrasound examination of all newborns' hips were performed using the Graf method on their first day of life. Results: Clinical sign of limited hip abduction showed significant predictive value for DDH. There were 67 (14.7%) newborns with the clinical sign of limited hip abduction, of which 26 (5.7%) were on the left hip, 11 (2.4%) on the right hip and 30 (6.6%) on both hips. Limited hip abduction had a positive predictive value (PPV) of 40.3% and a negative predictive value (NPV) of 80.4% for DDH. Conclusion: Limited hip abduction, especially unilateral, is a useful and important clinical sign of DDH. Doctors, who perform the first examination of the child after birth, would have to pay attention to this clinical sign. Newborns with this clinical sign would have to go to an ultrasound examination of the hips for further diagnosis.
Keywords: predictive value; limited hip abduction; developmental dysplasia of the hip (DDH)